2008
DOI: 10.1073/pnas.0705615105
|View full text |Cite
|
Sign up to set email alerts
|

Acute corticosterone treatment is sufficient to induce anxiety and amygdaloid dendritic hypertrophy

Abstract: Stress is known to induce dendritic hypertrophy in the basolateral amygdala (BLA) and to enhance anxiety. Stress also leads to secretion of glucocorticoids (GC), and the BLA has a high concentration of glucocorticoid receptors. This raises the possibility that stress-induced elevation in GC secretion might directly affect amygdaloid neurons. To address the possible effects of GC on neurons of amygdala and on anxiety, we used rats treated either acutely with a single dose or chronically with 10 daily doses of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
254
2
10

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(286 citation statements)
references
References 60 publications
20
254
2
10
Order By: Relevance
“…Our data appears to contradict the acute anxiogenic effect of CORT in the fear response (Mitra and Sapolsky, 2008) as increased CORT level was not linked to an increased fear response in GSM-exposed young adults. Indeed, this group rather displayed a tendency toward a decrease in response to the sound, which may be underlined by the fear-reducing effects of CORT, linked to its ability to inhibit the recall of previously acquired, emotionally arousing information (Roozendaal et al, 2009;Sartori et al, 2011).…”
Section: Gsm Exposure Stress and Emotional Memorycontrasting
confidence: 87%
“…Our data appears to contradict the acute anxiogenic effect of CORT in the fear response (Mitra and Sapolsky, 2008) as increased CORT level was not linked to an increased fear response in GSM-exposed young adults. Indeed, this group rather displayed a tendency toward a decrease in response to the sound, which may be underlined by the fear-reducing effects of CORT, linked to its ability to inhibit the recall of previously acquired, emotionally arousing information (Roozendaal et al, 2009;Sartori et al, 2011).…”
Section: Gsm Exposure Stress and Emotional Memorycontrasting
confidence: 87%
“…Additionally, it is interesting to note that individual differences in coping with predator stress -as manifested by post-stress anxiety responses in the elevated plus maze -were previously found in the literature to correlate with differences in the structure of the dendritic trees in the basolateral amygdala; thus, maladapted (extremely anxious) rats showed larger dendrites than welladapted (less anxious) animals (Mitra et al, 2009). Corticosterone treatment was found to mimic dendritic hypertrophy in the BLA and the enhanced anxiety observed after chronic stress (Mitra and Sapolsky, 2008). Differences in corticosterone responses and in neural activity in the amygdala were also previously found to be associated with coping responses to stress, with active coping leading to lower activation on those parameters (Walker et al, 2009).…”
Section: Discussionmentioning
confidence: 69%
“…Light pulses, constant light or dim light during the night may cause elevated GC levels in laboratory rats and mice, and in Nile grass rats [118][119][120][121][122][123], although in some cases, it was reported to have no effect or even decrease GC release [124,125]. It was recently reported that aberrant light may directly affect mood and cognitive functions in mice [123]; GC treatment was shown to increase anxiety and conditioned fear [126][127][128][129], and acute corticosterone elevation enhanced anti-predator behaviours in tree lizard species [130].…”
Section: (B) Masking Effect Of Moonlightmentioning
confidence: 99%
“…For example, in a light dark box test, GC treatment resulted in increased latency to leave the dark compartment, and in the elevated plus maze, it increased time spent in the sheltered arms [126][127][128][129]. Tree lizards treated with GC responded more quickly to predators and hid longer [130], and in the Adelie penguin (Pygoscelis adeliae) individuals with high pre-foraging corticosterone levels spent less time foraging, and stayed closed to the colony [131].…”
Section: (B) Masking Effect Of Moonlightmentioning
confidence: 99%